Pengaruh instrument HAM Internasional terhadap Undang Undang HAM di Indonesia - Nasution, Andreansyah Putra (Al Makki Publisher, 2025)
Human Rights Instruments are a reference as a foundation for the establishment of justice and the fulfillment of human rights as citizens. Human Rights Instruments (HAM) in the abstract refer to documents and legal regulations that regulate the protection and enforcement of basic human rights. These instruments can be national instruments (such as the Human Rights Act) or international (such as the Universal Declaration of Human Rights), which play an important role in ensuring that these rights are respected and protected in the sense of human rights. Human Rights are basic rights that are inherent in every individual since birth. Rights that are naturally irrevocable because they are a gift from God Almighty are one of the important aspects of human life.